Live Cell Imaging of Peptide Uptake Using a Microfluidic Platform - SARIYAR AKBULUT, BERNA (SPRINGER, 2021)
Cell penetrating peptides (CPPs) are unique molecules with the ability to pass through biological membranes as they carry their cargoes into the cells. Endocytosis and direct penetration have been proposed as the two major mechanisms for their internalization. However, the involvement of oligo peptide permease (Opp) in bacterial CPP uptake is an issue that yet remains to be elucidated. Here, a microfluidic platform coupled with live cell imaging was used to monitor CPP uptake in Escherichia coli. The set-up enabled imaging on a single-cell basis, helped to capture cell dynamics at a micro-scale and provided quantitative real-time information. The constructed platform also provided evidence on the contribution of Opp to peptide uptake. Additional high-resolution visualization under confocal microscopy confirmed that in the absence of Opp, the internalized peptides accumulated in the periplasm. Here, we have shown that microfluidic platforms, which have successful applications in different areas, can be used as a highly reliable and versatile tool for studying peptide uptake in bacterial cells.
Keywords: Microfluidics; Cell penetrating peptides; Peptide uptake; Live cell monitoring; E; coli; PENETRATING PEPTIDES; MECHANISMS